PENGGUNAAN POTENSI WILAYAH PERTANIAN SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR - Misbahul Munir (STAI Ma'had Aly Al-Hikam Malang, 2018)
Observation result in class IV A Madrasah Ibtidaiyah Mafatihul Huda Pujon Malang, it is known that learning is still dominated by teachers using the lecture method. Based on the results of observation, students feel bored, unhappy, and less motivated by the lecture method. From the lack of student motivation, it has an impact on the low student learning outcomes. The purpose of this study is to produce learning media that can improve student learning outcomes through the application of agricultural potential areas using five stages, namely (1) Needs analysis, (2) Study of basic competencies and learning materials, (3) Development of learning programs, (4) Production learning media, (5) Trial / product revision of learning media. The results of this study indicate that the use of the potential of agricultural areas as a learning media for â€œMakananku Sehat dan Bergiziâ€ subtheme in grade IV is very valid / feasible and student learning outcomes have increased. This is indicated by the test results (1) Media experts included in the assessment category are very valid / feasible with coefficient 0.96, (2) Learning design experts / teachers included in the assessment category are very valid / feasible with coefficient 0.92 (3) Small group trials included in the assessment category are very valid / feasible with coefficient 0.9. The learning outcomes of the student on the knowledge aspect increased from 45% in the pretest to 85% in the post test, the learning outcomes of the students on the attitudes increased from 65% in the pretest to 77% in the post test, and the learning outcomes of student on the skills increased from 64% in the pretest to 85% in the post test.